2020
DOI: 10.1021/acs.inorgchem.0c02907
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Benchmark Study on the Calculation of 29Si NMR Chemical Shifts

Abstract: A comprehensive and diverse benchmark set for the calculation of 29 Si NMR chemical shifts is presented. The SiS146 set includes 100 silicon containing compounds with 146 experimentally determined reference 29 Si NMR chemical shifts measured in nine different solvents in a range from −400 to +828 ppm. Silicon atoms bound to main group elements as well as transition metals with coordination numbers of 2−6 in various bonding patterns including multiple bonds and coordinative and aromatic bonding are represented.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 110 publications
3
26
0
Order By: Relevance
“…Conversely, the δSi for the SiMe3-substituted double bond silicon nuclei (87.9 ppm) is upfield-shifted compared to that of 3 (187.2). The substantial difference in the chemical shifts of the double bond silicon nuclei was reproduced qualitatively by the GIAO calculations of 5opt [73.1 (=SiSiMe3) and 237.7 (=Si(BBN•DMAP) ppm] and 3opt [209.1 (=SiSiMe3) and 136.2 (=Si(BBN) ppm] at the B97-D3/def2-TZVP [26] level of theory (Table S4). As Strohman, Kaupp et al have theoretically In the 29 Si NMR spectrum, two 29 Si resonances due to the unsaturated silicon nuclei [87.9 (=SiSiMe 3 ) and 195.2 (=Si(BBN•DMAP) ppm] were observed for 5.…”
Section: Reactions Of Boryldisilenes With 4-(nn-dimethylamino)pyridine (Dmap)mentioning
confidence: 74%
See 1 more Smart Citation
“…Conversely, the δSi for the SiMe3-substituted double bond silicon nuclei (87.9 ppm) is upfield-shifted compared to that of 3 (187.2). The substantial difference in the chemical shifts of the double bond silicon nuclei was reproduced qualitatively by the GIAO calculations of 5opt [73.1 (=SiSiMe3) and 237.7 (=Si(BBN•DMAP) ppm] and 3opt [209.1 (=SiSiMe3) and 136.2 (=Si(BBN) ppm] at the B97-D3/def2-TZVP [26] level of theory (Table S4). As Strohman, Kaupp et al have theoretically In the 29 Si NMR spectrum, two 29 Si resonances due to the unsaturated silicon nuclei [87.9 (=SiSiMe 3 ) and 195.2 (=Si(BBN•DMAP) ppm] were observed for 5.…”
Section: Reactions Of Boryldisilenes With 4-(nn-dimethylamino)pyridine (Dmap)mentioning
confidence: 74%
“…Conversely, the δSi for the SiMe 3 -substituted double bond silicon nuclei (87.9 ppm) is upfield-shifted compared to that of 3 (187.2). The substantial difference in the chemical shifts of the double bond silicon nuclei was reproduced qualitatively by the GIAO calculations of 5 opt [73.1 (=SiSiMe 3 ) and 237.7 (=Si(BBN•DMAP) ppm] and 3 opt [209.1 (=SiSiMe 3 ) and 136.2 (=Si(BBN) ppm] at the B97-D3/def2-TZVP [26] level of theory (Table S4). As Strohman, Kaupp et al have theoretically shown that the large difference in δSi of the double bond Si nuclei in the unsymmetrically substituted disilenes is mainly due to the spatial extent and orientation of the occupied and unoccupied molecular orbitals around the Si=Si double bond [27], the remarkable change in the δSi of the double bond Si nuclei upon coordination of DMAP is consistent with the lack of the conjugation between the π(Si=Si) and 2p(B) orbitals.…”
Section: Reactions Of Boryldisilenes With 4-(nn-dimethylamino)pyridine (Dmap)mentioning
confidence: 74%
“…The transition energies and oscillator strengths of the electron transition in hexane (Tables S5–S8) were calculated using a time-dependent hybrid DFT method (TD-DFT) at the B3LYP-D3/def2-TZVP (hexane) level of theory. The GIAO calculations for NMR chemical shifts (Table S6) were performed at the HCTH407/B1 (B1:6-311+G­(3d) [Si], 6-31G­(d) [other atoms] (benzene) or the B97-D3/def2-TZVP (benzene) level of theory. Natural bond orbital (NBO) analysis was performed using NBO 7.0 program (Tables S5).…”
Section: Methodsmentioning
confidence: 99%
“…As such, DHDF theory resides on the seamline between DFT and wavefunction approaches. DHDFs are the most accurate DFT methods available to date for main group energetics, [6][7][8] transition metal catalysis, [9][10][11][12] electronic excitation spectroscopy, [13][14][15][16][17][18][19][20][21] external magnetic [22][23][24][25] and electric field 26,27 induced properties, and vibrational frequencies. 28 Its reliance on a second-order perturbation theory term for part of the correlation energy creates an Achilles' Heel for molecules with small band gaps, due to the presence of orbital energy differences in the denominator.…”
Section: Introductionmentioning
confidence: 99%